The effect of two speed endurance training regimes on performance of soccer players - Iaia, F. M.; Fiorenza, M.; Perri, E.; Alberti, G.; Millet, G. P.; Bangsbo, J. (PLOS ONE, 2015)
In order to better understand the specificity of training adaptations, we compared the effects of two different anaerobic training regimes on various types of soccer-related exercise performances. During the last 3 weeks of the competitive season, thirteen young male professional soccer players (age 18.5±1 yr, height 179.5±6.5 cm, body mass 74.3±6.5 kg) reduced the training volume by ~20% and replaced their habitual fitness conditioning work with either speed endurance production (SEP; n = 6) or speed endurance maintenance (SEM; n = 7) training, three times per wk. SEP training consisted of 6-8 reps of 20-s all-out running bouts followed by 2 min of passive recovery, whereas SEM training was characterized by 6-8 x 20-s all-out efforts interspersed with 40 s of passive recovery. SEP training reduced (p<0.01) the total time in a repeated sprint ability test (RSAt) by 2.5%. SEM training improved the 200-m sprint performance (from 26.59±0.70 to 26.02±0.62 s, p<0.01) and had a likely beneficial impact on the percentage decrement score of the RSA test (from 4.07±1.28 to 3.55±1.01%) but induced a very likely impairment in RSAt (from 83.81±2.37 to 84.65±2.27 s). The distance covered in the Yo-Yo Intermittent Recovery test level 2 was 10.1% (p<0.001) and 3.8% (p<0.05) higher after SEP and SEM training, respectively, with possibly greater improvements following SEP compared to SEM. No differences were observed in the 20- and 40-m sprint performances. In conclusion, these two training strategies target different determinants of soccer-related physical performance. SEP improved repeated sprint and high-intensity intermittent exercise performance, whereas SEM increased muscles` ability to maximize fatigue tolerance and maintain speed development during both repeated all-out and continuous short-duration maximal exercises. These results provide new insight into the precise nature of a stimulus necessary to improve specific types of athletic performance in trained young soccer players.